The pollution status and environmental effects of Izmit bay (Marmara Sea, Turkey) crossing via tube tunnel or bridge - Akkoyunlu, A; Karpuzcu, M; Ertürk, F; Bayhan, H (Inst Lebensmitteltechnologie Analytische Chemie, 2002)
In Turkey, as a developing country, the environmental pollution problems have particularly increased since 1960, due to the rapid growth of industry and widespread increase of population in Marmara region, specifically in the Izmit bay. Since the 1960s, more than 250 large industrial plants have been built in the area surrounding the bay. In addition to the land and atmosphere, the bay is receiving the majority of these wastes. The pollution of Izmit bay has caused great concern to local and national authorities. In this study, environmental impact assessments of the two alternatives, crossing the bay via tunnel or bridge, have been investigated. Measurement of oceanographic parameters shows the presence of a two-layer water body with seasonal variation in the bay. At project route surface concentrations of dissolved oxygen were found to be at their saturation values, whereas they drop down to 0.7 mg/l at the bottom. Polychaeta, species in the deep sludge characterized a retarding ecological system. The fauna species, observed in the benthic structure, would again be recovered after development the crossing via tube or bridge. The dredged material obtained from the bay crossing route can be used in sanitary land filling sites of Gebze. The most inconvenient conditions in terms of air pollution seemed to be caused by tube crossing the bay.
Keywords: Izmit Bay; oceanography; benthic; sediment; dredged material; air quality